Building Material in The Perspective of Energy Efficiency and Thermal Environment in TOD Area. Issue 1 (July 2020) - Muhammad, Fadhil; Wonorahardjo, Surjamanto
Abstract: The development of urban area such as a Transit Oriented Development (TOD) involves a lot of building materials that are forming the physical environment which rises problems of urban heat island (UHI) and energy consumption. The TOD forming urban corridors that rise urban canyon issues with high air temperature, poor air quality, high energy consumption for air cooling and purifying (HVAC). The common heavyweight building materials that dominate the physical environment of TOD and other urban areas have low specific heat and high heat capacity. Another thermal property of concrete and brick storing the heat energy influence the air temperature during the night. The lightweight modern building materials that are cheap in construction cost show the worse phenomenon in the UHI perspective due to its lower specific heat. This review paper discusses the role of building material in the urban thermal environment such as the TOD area in the energy and environment perspective. The early result shows that both heavyweight and lightweight modern building material have a bad performance for the environment and should be mitigated otherwise our future will become worse. The energy consumption that rises uncontrollably due to bad air quality and high temperature will decrease the liveability level of the urban area.